Osteopetrosis and Osteomyelitis-Their Secret Bond (Indian Journal of Contemporary Dentistry, 2025)
Background: Osteopetrosis, is characterized by a spectrum of conditions marked by increase in bone density due to defective osteoclast activity, leading to fragile bones, hematologic issues, nerve entrapment leading to growth challenges. On the other hand, osteomyelitis is an inflammatory process of bone and bone marrow caused by an infectious-organisms which results in local bone destruction, necrosis and apposition of new bone. Case report: This article discusses a case of a 32-year-old male initially diagnosed with maxillary osteomyelitis who presented with a draining fistula in the posterior maxilla for seven months. After a thorough combination of history, clinical, radiographic, and laboratory findings, it was discovered that the patient also had osteopetrosis. The hidden connection between the two conditions suggests that osteopetrosis may often go undiagnosed in patients presenting with osteomyelitis.Conclusion: This case underscores the diagnostic challenges posed by overlapping pathologies such as osteomyelitis and osteopetrosis, particularly within the craniofacial region. The co-occurrence revealed in this patient emphasizes the need for heightened clinical suspicion and a multidisciplinary approach when evaluating persistent maxillofacial infections. Early recognition of underlying osteopetrosis is essential for appropriate management and may prevent prolonged morbidity.
Keywords: Bone fractures, Maxillofacial disorders, Osteomyelitis, Osteopetrosis.